THE IMPACT OF NATURAL ENVIRONMENT ON CHINESE LANDSCAPE PAINTING - Chu Fan; Wan Samiati Andriana W. Mohamad Daud; Valerie Anak Michael; Huajin Zhang, (INTERNATIONAL JOURNAL OF HERITAGE, ART AND MULTIMEDIA (IJHAM), 2024)
Chinese landscape painting, as a gem in Chinese art, is deeply influenced by the natural environment. This study conducts a comprehensive analysis through historical literature, classical artworks, and expert interviews to explore the profound impact of the natural environment on Chinese landscape painting. The research reveals that artists, across different historical periods, express reverence for nature and a sense of integration with it in their works. This influence is not only evident in the artworks but, through an in-depth exploration of artists' experiences, also provides valuable insights for the development of contemporary landscape painting. Through a thorough and detailed study, this paper broadens the understanding of Chinese landscape painting, offering a new perspective for the in-depth exploration of the field of art.